2003
DOI: 10.1074/jbc.m301820200
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Expression of Leukemia Inhibitory Factor Induces B Cell Hyperplasia and Confers Protection in Hyperoxia

Abstract: Leukemia inhibitory factor (LIF) is produced by a large number of pulmonary cells in response to diverse stimuli. Exaggerated levels of LIF have also been detected in the adult respiratory distress syndrome and other disorders. The biologic effects of LIF in the lung, however, have not been elucidated. To define the respiratory effects of LIF, we generated transgenic mice in which human LIF was selectively targeted to the mature lung. In these mice, transgene activation caused an impressive increase in broncho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 36 publications
4
24
0
Order By: Relevance
“…In accord with studies from our laboratory and others, WT mice died after 3-6 days of exposure to 100% O 2 (11)(12)(13)(14)16). In this setting, 50% of WT mice were dead after 4.5 days and 100% had died by day 5.5 ( Fig.…”
Section: Role Of Il-13 In Halisupporting
confidence: 62%
See 2 more Smart Citations
“…In accord with studies from our laboratory and others, WT mice died after 3-6 days of exposure to 100% O 2 (11)(12)(13)(14)16). In this setting, 50% of WT mice were dead after 4.5 days and 100% had died by day 5.5 ( Fig.…”
Section: Role Of Il-13 In Halisupporting
confidence: 62%
“…In the normal and injured lung, the severity and consequences of oxidant injury are modulated by generalized and tissue-specific protective mechanisms. Previous studies from our laboratory and others demonstrated that exogenously administered cytokines, including IL-13, confer tissue cytoprotection in HALI (11)(12)(13)(14). Surprisingly, the role(s) that endogenous IL-13 plays in the control of these oxidant-induced responses has not been adequately defined.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…IGF-I, and to a lesser extent LIF, are factors known as general inductors of cell proliferation in a variety of tissues, including the lung. Thus, transgenic mice overexpressing either IGF-I or LIF in the adult lung depict hyperplasia of certain cell types (Wang et al, 2003;Frankel et al, 2005). Paradoxically, the progressive lung hypoplasia observed in E18.5 Igf-I nulls and Lif/Igf-I double-nulls is accompanied by a progressive increase in lung proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Mice (4-6 wk old) were placed in cages in an airtight Plexiglas chamber (55 3 40 3 50 cm), as described previously (6,10,32). Throughout the experiment, they were given free access to food and water.…”
Section: Oxygen Exposurementioning
confidence: 99%